MEMES E EDUCAÇÃO MIDIÁTICA: A LEITURA E ESCRITA MEMÉTICA EM PROCESSOS DE ENSINO E APRENDIZAGEM - Barreto, Carlos Henrique da Costa (2024)
This work is developed in the context of the Digital Universe and contemplates, in a proposal for educational union, two of its byproducts: Memes and Media Education. Despite its conceptual origin in 1976, in Biology, memes have become a popular phenomenon of internet culture as a form of language characteristic of its social layer that works, through humor, the synthesis of diverse contents, good or bad, demanding study and critical vision. Especially when we think about its use as a language in teaching. In this perspective, Media Education stands out as a contemporary branch of education to educate people to live responsibly with media-digital transformations and products, with guidance from 3 Axes: Reading, Writing, and Participation. Each axis is endowed with specific skills and abilities to be developed for a full exercise of digital citizenship. Therefore, we delimit the problem: how can the reading and interpretation of memes potentiate contemporary teaching and learning processes? To this end, this work aims to explore the possibilities of memes, through Media Education, as an object that potentiates these processes. It is a qualitative, exploratory, and descriptive work divided into two moments: theoretical, in the construction of a reference framework to support our theme; and practical, in a Media Education activity addressing memes, in Higher Education, to understand how the processes of memetic reading and writing take place, and thus answer our problem. As results, we were able to understand the different ways in which students appropriate the language, structure, and particularities of memes to interpret (read) and produce (write) memes, combining such skills for general performance (participation) in their daily contexts. We were able to answer that memes potentiate teaching and learning by acting as a facilitating agent for the coding and decoding of educational content and knowledge through their language without neglecting their qualities of humor – with guidance based on the 3 Axes of Media Education.